2022
DOI: 10.1101/2022.10.28.514187
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Formation and three-dimensional architecture ofLeishmaniaadhesion in the sand fly vector

Abstract: Attachment to a substrate to maintain position in a specific ecological niche is a common strategy across biology, especially for eukaryotic parasites. During development in the sand fly vector, the eukaryotic parasiteLeishmaniaadheres to the stomodeal valve, as the specialised haptomonad form. Dissection of haptomonad adhesion is a critical step for understanding parasite transmission. Nevertheless, haptomonad studies are limited, as this is a technically challenging life cycle form to investigate. Here, we h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Propidium iodide (PI) quantitatively stains DNA (S2A,B Fig), but requires cell fixation, and is thus unsuitable for use in live cells. Hoechst 33342 is commonly used to stain the nucleus and kinetoplast in live Leishmania (4042), but IFC indicated that it does not bind proportionally to DNA (S2C Fig). Images of Hoechst-stained cells revealed staining outside of the nucleus that may account for it being non-quantitative (S2C Fig).…”
Section: Resultsmentioning
confidence: 99%
“…Propidium iodide (PI) quantitatively stains DNA (S2A,B Fig), but requires cell fixation, and is thus unsuitable for use in live cells. Hoechst 33342 is commonly used to stain the nucleus and kinetoplast in live Leishmania (4042), but IFC indicated that it does not bind proportionally to DNA (S2C Fig). Images of Hoechst-stained cells revealed staining outside of the nucleus that may account for it being non-quantitative (S2C Fig).…”
Section: Resultsmentioning
confidence: 99%
“…Haptomonad adhesion occurs via the heavily modified parasite flagellum, in which an attachment plaque is positioned adjacent to the flagellum membrane from which filaments extend towards the cell body and specific connections to the stomodeal valve are formed 11 . Leishmania is closely related to other kinetoplastid parasites that cause disease in humans.…”
Section: Figurementioning
confidence: 99%
“…Leishmania adhesion proceeds through a series of defined steps, from initial adhesion, to flagellum disassembly and final maturation of the plaque 11 . To understand the point at which the different KIAPs appeared, we examined cells at different stages of adhesion (Fig.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations